Modulation of Autophagy by SARS-CoV-2: A Potential Threat for Cardiovascular System - Randhawa, Puneet Kaur; Scanlon, Kaylyn; Rappaport, Jay; Gupta, Manish K. (Frontiers in Physiology, 2020)
Recently, we have witnessed an unprecedented increase in the number of patients suffering from respiratory tract illness caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The COVID-19 virus is a single-stranded positive-sense RNA virus with a genome size of 29.9 kb. It is believed that the viral spike (S) protein attaches to angiotensin converting enzyme 2 cell surface receptors and eventually, the virus gains access into the host cell with the help of intracellular/extracellular proteases or by the endosomal pathway. Once, the virus enters the host cell, it can either be degraded via autophagy or evade autophagic degradation and replicate using the virus encoded RNA dependent RNA Polymerase. The virus is highly contagious and can impair the respiratory system of the host causing dyspnea, cough, fever, tightness in the chest. This disease is also characterized by an abrupt upsurge in the levels of proinflammatory/inflammatory cytokines and chemotactic factors in a process known as cytokine storm. Certain reports have suggested that COVID-19 infection can aggravate cardiovascular complications, in fact, the individuals with underlying co-morbidities are more prone to the disease. In this review, we shall discuss the pathogenesis, clinical manifestations, potential drug candidates, the interaction between virus and autophagy, and the role of coronavirus in exaggerating cardiovascular complications.